The application of lean manufacturing for standardization of the canned chicken production process in Peru food companies - Romani Rey, Alessandro Emmanuel (2024)
In Peru, chicken is one of the most consumed foods in all regions. Due to the constant increase in population,chicken production is increasing in the country. For this reason, a food company must improve its efficiency to satisfy more customers and reduce its costs per productive unit without reducing its quality. The research can be useful to canning companies as well as companies where their machines suffer from many failures within production due to a lack of maintenance planning and worker training. The model used is based on two methodologies: 5S and TPM. These methodologies reduced the total production time per batch by 8% and improved the utilization rate by 7 percentage points. The use of these tools helped reduce corrective maintenance time and standardize processes to avoid recurring equipment failures.